1986
DOI: 10.1139/o86-171
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of mitochondrial macromolecules in herpes simplex type 1 virus infected Vero cells

Abstract: How viral infections affect host cell mitochondrial functions is largely unknown. In this study, uptake of radiolabeled precursors was used to assess how a herpes simplex virus type 1 (HSV 1) infection influences synthesis of macromolecules comprising Vero cell mitochondria. Total macromolecular synthesis in infected cells was determined for comparative purposes. Mitochondrial and total cellular DNA syntheses were approximately halved at 1-2.5 h postinfection (PI). Mitochondrial DNA synthesis in infected cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Herpes simplex viruse infection of the cell has been known to degrade the mitochondrial DNA (mtDNA) rapidly and completely by an HSV nuclease, UL12 gene product (Saffran et al, 2007). This is in compliance with the early findings where the production of mitochondrial proteins decreased by 60% in HSV-infected cells when compared to the uninfected cells (Lund and Ziola, 1986;Latchman, 1988). In another study, the mitochondrial damage has been associated with encephalitis caused by HSV infection.…”
Section: Maintenance and Exploitation Of Mitochondria Until Mid-herpesupporting
confidence: 73%
“…Herpes simplex viruse infection of the cell has been known to degrade the mitochondrial DNA (mtDNA) rapidly and completely by an HSV nuclease, UL12 gene product (Saffran et al, 2007). This is in compliance with the early findings where the production of mitochondrial proteins decreased by 60% in HSV-infected cells when compared to the uninfected cells (Lund and Ziola, 1986;Latchman, 1988). In another study, the mitochondrial damage has been associated with encephalitis caused by HSV infection.…”
Section: Maintenance and Exploitation Of Mitochondria Until Mid-herpesupporting
confidence: 73%
“…Interestingly, levels of cellular ATP and lactate as well as Δψ m are maintained for at least 6 h after infection before decreasing at later stages (Murata et al, 2000a). Earlier studies demonstrated that mitochondrial protein synthesis in HSV-infected cells decreases progressively, dropping to about 60% of normal levels (Latchman, 1988;Lund and Ziola, 1986). Moreover, mitochondria exhibit a gradual decline in the rate of calcium uptake, which reaches 65% of the control rate at later stages of infection (Lund and Ziola, 1985).…”
Section: Hsv Affects Intracellular Compartmentalization Of Mitochondriamentioning
confidence: 95%
“…If that is the case, the acquisition by ASFV of a prenyltransferase gene for the synthesis of the ubiquinone (coenzyme Q) prenyl chain could be related to an increase in mitochondrial function that might be required to provide extra energy for viral processes, such as macromolecular synthesis and morphogenesis. In this connection, it should be mentioned that mitochondrial DNA synthesis has been found to increase in herpes simplex type 1 virus-infected Vero cells (57) and that adenovirus infection of human cells stimulates mitochondrial activity (58).…”
Section: Properties and Transcriptional Analysis Of Orf B318l-mentioning
confidence: 99%